Analisis Strategi Penggunaan APBD dan DAK dalam Pengembangan Pariwisata Kabupaten Ponorogo - Nafa Fadhilatul Latifah; Gita Aulia Rohmah; Eva Hany Fanida; Melda Fadiyah Hidayat (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study examines the effectiveness of the Regional Budget (APBD) and Special Allocation Fund (DAK) in the tourism sector of Ponorogo Regency, as well as their impact on the growth of Regional Own Revenue (PAD). The study’s relevance is strengthened by Ponorogo’s recognition as a member of UNESCO Creative Cities Network (UCCN) in 2024 through the Reog performing art, which opens considerable opportunities for culture-based tourism development. A qualitative descriptive method is employed using a documentation study approach, drawing on APBD realization reports, DAK implementation records, BPS statistical data, and regional planning documents. The analytical framework is grounded in public budget effectiveness theory and its alignment with SDG 8 (decent work and economic growth), SDG 11 (sustainable cities and communities), and SDG 17 (partnerships for the goals).